A influência de diferentes tipos de matriz na guilda de borboletas frugivoras (Insecta: Lepidóptera) em fragmentos de Mata Atlântica - Brito, Mariana Monteiro De (2013)
For butterflies, tolerance to the matrix may be another important criterion of habitat occurrence in fragmented landscapes. Here we examine the relative effects of habitat fragmentation and agricultural matrix in the surrounding on fruit-feeding butterfly functional composition in the Atlantic rain forest of southeastern Brazil. Generalized linear models were used to detect the effects of landscape metrics on butterfly richness and abundance of the total assemblage and functional groups and circular statistics was used for analyzed the patterns of monthly abundance of the total assemblage and functional groups in the forest remnants and the surrounding matrices. In total, 650 butterflies representing 57 species were captured and species composition differed significantly between the forest fragments and the surrounding matrices. We recorded 23 forest specialists, 18 matrix-tolerant species and 16 did not show habitat preferences. Richness and abundance of forests species were best predicted with the proximity and size of surrounding forest fragments, while matrix-tolerant and generalists without habitat preference were particularly sensitive to forest fragment shape and the percentage of surrounding matrices, especially pastures. Circular analysis revealed that forest specialist species were concentrated in the rainy season (September - March) while matrix-tolerant species concentrated in April-August. Moreover, generalist without habitat preference showed lower seasonality than specialists. Although maintaining connectivity of forest fragments may increase the mobility and dispersion of some species, our results show that it is important only for forest specialists. However, our results suggest that management recommendations may have different impacts depending on which functional group of fruit-butterflies is being considered.